2003
DOI: 10.1002/hec.823
|View full text |Cite
|
Sign up to set email alerts
|

Fixed fees and physician‐induced demand: A panel data study on French physicians

Abstract: This paper investigates on the existence of physician-induced demand (PID) for French physicians. The test is carried out for GPs and specialists, using a representative sample of 4500 French self-employed physicians over the 1979-1993 period. These physicians receive a fee-for-services (FFS) payment and fees are controlled. The panel structure of our data allows us to take into account unobserved heterogeneity related to the characteristics of physicians and their patients. We use generalized method of moment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
63
1
6

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 24 publications
3
63
1
6
Order By: Relevance
“…Birch (2), Grembowski et al (3), Porter et al (4), and Chalkley and Tilley (5), suggest evidence of induced demand by dentists in specific cases. Evidence also exists in the case of physicians, a similar group of professionals, as described by Grytten (6), Izumida et al (7), Delattre and Dormont (8), and Xirasagar and Lin (9). Woods et al (10) found that dentists providing oral health services in the DTSS were influenced by both economic incentives and system changes.…”
Section: Introductionmentioning
confidence: 93%
“…Birch (2), Grembowski et al (3), Porter et al (4), and Chalkley and Tilley (5), suggest evidence of induced demand by dentists in specific cases. Evidence also exists in the case of physicians, a similar group of professionals, as described by Grytten (6), Izumida et al (7), Delattre and Dormont (8), and Xirasagar and Lin (9). Woods et al (10) found that dentists providing oral health services in the DTSS were influenced by both economic incentives and system changes.…”
Section: Introductionmentioning
confidence: 93%
“…With respect to quality of care, theory predicts that competition improves quality only in case quality elasticity is large compared to price elasticity, which remains an empirical question (Dranove andSatterthwaite 2000, Gaynor 2006). Also empirical studies are not consistent in their finding of an impact of competition on inducing behavior (Delattre and Dormont 2003, Carlson and Grytten 1998, Schaumans 2008) nor on quality of care (Sorensen andGrytten 1999, Pike 2010). Finally, Godager et al (2012) finds negligible or small positive effects on referrals to medical specialists, while Iversen and Ma (2011) find a positive impact of competition on radiology referrals .…”
Section: Introductionmentioning
confidence: 97%
“…7 Delattre and Dormont (2003) make this point with regard to France. 8 See Noguchi and Shimizutani (2005), which used the same dataset, for more detailed information.…”
Section: Description Of the Datamentioning
confidence: 96%